Volume 5: Energy Systems Analysis, Thermodynamics and Sustainability; NanoEngineering for Energy; Engineering to Address Climat 2010
DOI: 10.1115/imece2010-40598
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Compliant Foil Bearing and Seal Technologies in Support of 21st Century Compressors and Turbine Engines

Abstract: For energy independence to become a reality, whether through the more effective use of US natural resources such as natural gas or through the continued development of the hydrogen economy, efficient and reliable large-scale compressors are needed to enhance the existing pipeline infrastructure that moves energy storing gases from production sites to end user locations. Oil-free, non-contacting seal and bearing technologies are critical to the successful development of new high efficiency and power dense compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Under extreme operating conditions such as high rotating speed and high medium pressure, the rigid surface of end face gas seal is prone to rubbing and crushing. Compliant foil face gas seal (CFFGS) with gas as the lubricating medium shows important application value in the shaft end seal of centrifugal compressors, aero-engines, and other turbomachinery, with its significant advantages such as high temperature resistance, impact resistance, excellent leakage control, and strong adaptability [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under extreme operating conditions such as high rotating speed and high medium pressure, the rigid surface of end face gas seal is prone to rubbing and crushing. Compliant foil face gas seal (CFFGS) with gas as the lubricating medium shows important application value in the shaft end seal of centrifugal compressors, aero-engines, and other turbomachinery, with its significant advantages such as high temperature resistance, impact resistance, excellent leakage control, and strong adaptability [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Muson et al [11,12] verified that CFFGS has excellent adaptability and leakage control performance under extremely highspeed and high-temperature conditions. The test results of Heshmat et al [4,13] based on aircraft air circulation machines and hydrogen centrifugal compressors show that CFFGS is a high-efficiency gas sealing technology with low leakage and low wear. Research by Muson [5] shows that CFFGS has important applications in turbine shaft-end seals.…”
Section: Introductionmentioning
confidence: 99%
“…Heshmat and Walton 17 put forward a theoretical prediction formula for the leakage rate of CFFGS, and experimentally explored the influence of structural parameters on the leakage rate. Heshmat et al 18 explored the coordination between film pressure and foil deformation based on finite difference and finite element analysis, and experimentally proved that CFFGS is a low-leakage and high-efficiency gas face sealing technology for new hydrogen centrifugal compressors. Muson, 19 in a test based on the Rolls-Royce gas turbine platform, found CFFGS to be of great value for applications in gas turbine rotor thrust balance structures and turbine rims.…”
Section: Introductionmentioning
confidence: 99%
“…Both static and dynamic testing were performed on the seals using air and helium at operating speeds up to 60 krpm. The results of these tests, in which various seal parameters were varied, indicated that very low values could be obtained for the flow factors used to characterize seal leakage [41]. It was then demonstrated that performance capabilities of the designed centrifugal hydrogen compressor met the needs for the pipeline delivery of pure hydrogen [42].…”
Section: Introductionmentioning
confidence: 99%
“…The work of the lead author and his research team is also recognized for its simultaneous developments in the theoretical realm, experimental methods and results, and in the methods needed to successfully apply foil bearings and seals in advanced oil-free rotating machinery. These works have resulted in a better understanding of the performance, design and application methodology of compliant foil bearings/seals, as well as the development of better analytical tools to integrate advanced foil bearings/seals into high performance propulsion and power generation systems [17][18][19][20][21][22][23][24][25][26][27]. These advanced foil bearings with improved load and temperature performance having variable compliant structures in all three dimensions and time-dependant damping and stiffness are designated as 4th generation foil bearings.…”
Section: Introductionmentioning
confidence: 99%